Digital technologies in management of chronic pain- a systematic review - Hussain, Afshan; Husna Haroon; Ashfaq Ahmed; Syed Amir Gilani (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the effectiveness of digital health technologies in the management of chronic pain. Methods: The systematic review comprised search for randomised controlled trials and controlled clinical trials involving patients with chronic pain published between 2010 and 2020. The search was conducted on PubMed, Google Scholar, MEDLINE, National Centre for Biotechnology Information, and National Library of Medicine databases. Risk bias tool was used to evaluate the biasness in the studies and Pedro scale was used to assess the quality of the included articles. Results: Of the 33 articles fully assessed, 14(42.42%) were analysed. All the studies analysed were randomised controlled trials and scored 6-10 on the Pedro scale which showed high quality of methodology. The studies typically reported statistically significant benefits of digital health technologies in the management of chronic pain. One of the main benefits was enhanced pain coping skills of the patients. Additionally, majority of the studies included increased adherence to exercise as an essential advantage. Conclusion: All the studies analysed reported favourable conclusions regarding the use of digital intervention for chronic pain management. Key Words: Chronic pain, Digital intervention, Health technologies, Pain management, Randomised controlled trial.